Intracorporeal lithotripsy - Alken, Peter (Urolithiasis, 2018)
Since the introduction of ESWL, PNL and URS during the early 1980s the application rate of ESWL has declined while those of PNL and URS have increased. This is mainly due to the facts that instruments and techniques for Intracorporeal Lithotripsy (IL) have made a continuous progress. This review shows that today an array of options for IL within the entire urinary tract is available to treat stones in a perfect minimal invasive way. At the same time further improvements of IL are already visible.
Gesehen am 04.10.2019
Published online: 4 December 2017